INDONESIAN ECONOMIC DEMOCRACY: DEBATES, CHALLENGES AND OPPORTUNITIES - Zulkifli Zulkifli (Tatar Pasundan: Jurnal Diklat Keagamaan, 2022)
The Pancasila Economic Democracy's adoption encountered significant cultural and psychological barriers. Democratic economic models have not yet produced sufficient outcomes. Contrarily, liberal capitalistic democracy is being practiced in this context.  This article discusses Economic Democracy as Indonesia’s economic system. This research is a library with a descriptive approach that collects documentation data from various articles and books and analyzed it through content analysis. This research’s results must balance planning between national and decentralization levels in implementing economic activities to reach economic and social justice. In addition, Indonesia can also build a more rational foundation of the peculiarities of economic activity so that it is not limited to religious values but involves cognitive awareness to realize ideals as stated in the Preamble of the UUD 1945. Current capability is viewed as a deficit that could become a tremendous strength in the future so that individuals will not be frightened of being different or taking risks.Keyword: Indonesia; Economic Democracy; The Concept and Reality of Failure.